A siker szociális reprezentációja - értelmiségi rétegeknél - Váriné Szilágyi, Ibolya; Solymosi, Zsuzsa (Szociológiai Szemle, 2024)
Cognitive representations of social success, bearing the cultural and stratum specific features upon themselves, do change in societies striving to modernize, but from the angle of progression it is not at all indifferent how. Hungary is not an exception either, where after the changes of the 90s the results of research, informing about the ideas related to social and personal success of the intellectuals playing a decisive role in modernization, may be particularly interesting and perhaps even useful. Actually these ideas have several functions: they are indicators of a condition as well as (strengthening or weakening) motivations in the current process of modernization. The present research attempted to explore the social representatives of success with the means of cognitive social psychology among future and practising representatives of three such strata of intellectuals (agricultural engineer, architect and economist), who have had different chances of success prior to and after the systemic change. The paper presents only a part of the complex survey conducted by questionnaire, namely the series of factors and characteristics (causal attributions) supposed to stand behind the success of the successful individual personally known by the respondent and the success of the generalized successful Hungarian person together with the significant differences between the factors organizing the social representations of success and the genders, professions and generations standing for them. Of the two kinds of image of success the picture of the successful Hungarian was primarily conspicuous of a negative emotional charge, particularly in the sub-sample of undergraduates. The know successful individual was almost exclusively male (mostly chosen from the economic sphere), which remarkably preserves past beliefs even if otherwise there had been no comprehensive difference between genders. There has been no such difference among the various professions as contrasted to differences among generations (particularly in respect of achievement, standards of information and the ability to communicate, apparently assessed in a more complex manner by experts).